Measuring the Performance of Fiscal Policy in Russia - Spilimbergo, Antonio (International Monetary Fund, 2005)
This paper evaluates the performance of fiscal policy in Russia since the 1998 crisis along several dimensions, using a variety of indicators. Russia has progressed tremendously in recent years on public debt sustainability, largely thanks to the fact that the real interest rates on public debt have been negative and growth has been high. However, the constant oil-price balance shows a progressive worsening starting in 2001, with a modest reversal in 2004. The analysis of the non-oil fiscal balance shows that Russian fiscal policy has had a mixed record. Part of the windfalls were spent before the introduction of the oil stabilization fund, but most of the oil revenues have been saved during the last two year. This poses an important challenge for future years when the automatic saving mechanism provided by the oil stabilization fund will be weakened by the approved increase in the reference oil price. The standard fiscal impulse shows that budget policy has not contributed to the increase in aggregate demand since 2003. However, the fiscal position was not tight enough to contain the inflationary effects of the exceptional oil windfalls on the economy as a whole